Problem Solution in Cultural Differences Between Sundanese and non Sundanese Couple in Bandung by Using Intercultural Communication - Christina Rochayanti (The Indonesian Journal of Communication Studies, 2008)
Interethnic marriage means legal union of spouse from different ethnic group. It is a form of cultural background differences at interpersonal level (micro). Besides, starting their new marriage life, the couple must also adjust themselves respectively toward different cultural elements. The method of the research is interpretive-qualitative with symbolic interaction approach. Participants of the research were selected from those who have been through the process of cultural adjustment in interethnic marriage. Data was collected by deeply interviewing and observing 13 couples, Sundanese and non-Sundanese that have been married for more than 10 years and have children. Generally, the research shown that Sunda cultural and custom of couples’ ethnic identity difference formed a communication interethnic marriage patterns Sundanese and non Sundanese in Bandung. The results of the research were divided into three findings : firstly the communication patterns of interethnic marriage can be classified into; (1) dominant, (2) initiative, (3) combination, (4) adaptive, and (5) creative. Secondly, various pressures in the interethnic marriage life mainly caused by financial support for their extended family, different food appetite, life style and social comments. Thirdly, the interethnic couples can accommodate the differences in treating their children and interacting with their extended family.